Pediococcus pentosaceus, a future additive or probiotic candidate - Jiang, Shiman; Cai, Lingzhi; Lv, Longxian; Li, Lanjuan (Microbial cell factories, 2021)
Background Pediococcus pentosaceus , a promising strain of lactic acid bacteria (LAB), is gradually attracting attention, leading to a rapid increase in experimental research. Due to increased demand for practical applications of microbes, the functional and harmless P. pentosaceus might be a worthwhile LAB strain for both the food industry and biological applications. Results As an additive, P. pentosaceus improves the taste and nutrition of food, as well as the storage of animal products. Moreover, the antimicrobial abilities of Pediococcus strains are being highlighted. Evidence suggests that bacteriocins or bacteriocin-like substances (BLISs) produced by P. pentosaceus play effective antibacterial roles in the microbial ecosystem. In addition, various strains of P. pentosaceus have been highlighted for probiotic use due to their anti-inflammation, anticancer, antioxidant, detoxification, and lipid-lowering abilities. Conclusions Therefore, it is necessary to continue studying P. pentosaceus for further use. Thorough study of several P. pentosaceus strains should clarify the benefits and drawbacks in the future.